Use of Pareto Principle in Power System Mode Analysis - Mahnitko, Anatoly; Gavrilov, Alexander (Electrical, Control and Communication Engineering, 2010)
The optimal power dispatch problem in the power system is looked out in the given work. The mathematical model of power system optimal regime searching approach in the market conditions in accordance with Pareto principle is described. The theoretical layout is illustrated on a real power system model of the united power system, which consists of 17 nodes and 21 lines. The procedure is realized using the GAMS software.